Implicit Mann Type Iteration Method Involving Strictly Hemicontractive Mappings in Banach Spaces - Arif Rafiq; Shin Min Kang (Journal of Applied Mathematics)
We proved that the modified implicit Mann iteration process can be applied to approximate the fixed point of strictly hemicontractive mappings in smooth Banach spaces.